Strengthening Pedagogical Content Knowledge of Prospective Chemistry Teacher: Metacognitive Based Preparation Program for Students’ Self-Efficacy - Eda Lolo Allo; Anna Permanasari; Wiji Wiji; Sri Redjeki (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2021)
The self-efficacy of prospective teachers is fostered through a program to prepare prospective teachers. Self-efficacy is one factor that influences personal and professional development in the future to become a professional teacher. The research aimed to investigate the impact of metacognition preparation in designing learning programs on prospective chemistry teachers' self-efficacy. Descriptive qualitative research is used as a method to interpret the data obtained. The subjects of this study were 34 students of the fifth semester of the Chemistry Education Department of the 2019/2020 academic year at one of the LPTKs in the city of Makassar. Data collection was carried out using a self-efficacy questionnaire adapted from the Science Teaching Efficacy Belief Instrument-Pre service (STEBI-B), which includes the dimensions of Personal Science Teaching Efficacy (PSTE) and Science Teaching Outcome Expectancy (STOE). The questionnaire data were analyzed by means of the average class score. The results showed that the metacognition debriefing program in designing learning could increase student self-efficacy as seen from the increase in the average class score at four stages of implementation, namely: 61.5; 66.1; 67.9; and 72.2. The students' average self-efficacy scores on the PSTE dimension were: 33.5; 38.2; 39.0; 41.8. The mean score of student self-efficacy in the STOE dimension was 28.0; 28.0; 28.9; 30.4. Student self-efficacy increased in both dimensions with higher PSTE scores than STOE scores.